Heat transfer characteristics for multi-silicon ingots irradiation in a typical research reactor - Said M.A. Ibrahim; Abdelfatah Abdelmaksoud; W. Helal (International Journal of Thermofluids, 2023)
A computational fluid dynamics (CFD) study is conducted for silicon ingot irradiation facility in a typical material testing reactor (MTR). The ingots are placed inside the irradiation device in staggered and in-line bundles. The configurations are varied according to the variations of longitudinal and transverse pitches Sl and St, respectively. For in-line bundles, Sl and St are changed in the range of 1.1, 1.2, 1.3, 1.4, and 1.5 of the ingot diameter. For staggered bundles, Sl is changed in the range of 1.1, 1.2, 1.3, 1.4, and 1.5 of the ingot diameter while St is changed in the range of 0.95, 1.0, 1.05, 1.1, and 1.15 of the ingot diameter. The silicon ingot volumetric heat generation Qv is allowed to change around its nominal value in the range of 0.25, 0.5, 0.75, 1.0, and 1.25 W/g. The effects of rotation of ingots during irradiation at velocities of 15, 30, and 60 rpm are investigated. The computational fluid dynamics code ANSYS FLUENT is employed to carry out the calculations. The temperature profile inside the silicon ingot during irradiation is of significant importance for uniform doping. Therefore, the impact of heat generation and bundle pitches on the temperature profile through the ingot is calculated and reported for all cases of this study. The results show that the maximum ingot temperature does not exceed the limits for each bundle at maximum heat generation. Two correlations for average Nusselt number for both aligned and staggered configurations are generated to describe heat transfer rates during natural convection regime. The rotation of ingots during irradiation showed considerable enhancement of heat transfer rates.